2012
DOI: 10.4103/1947-2714.104313
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and other cardiovascular risk factors among police officers

Abstract: Background:Police force constitutes a special occupational group. They have been shown to be at high risk for the development of cardiovascular diseases. A multitude of factors may be responsible for this. There is very limited documentation of their health status and health surveillance activities are inadequate.Aim:The present study was designed to measure the prevalence of metabolic syndrome and other cardiovascular risk factors among police officers.Materials and Methods:The design was cross-sectional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
68
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 17 publications
(28 reference statements)
11
68
2
3
Order By: Relevance
“…5 In contrast a recent study in Kerala found the prevalence rate of hypertension to be 37.7%. 3 In view of the above, the prevalence may be comparable or marginally higher than other risk groups or general population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 In contrast a recent study in Kerala found the prevalence rate of hypertension to be 37.7%. 3 In view of the above, the prevalence may be comparable or marginally higher than other risk groups or general population.…”
Section: Discussionmentioning
confidence: 99%
“…2 Police personnel constitute a special occupational group with exposure to violence and stress at work, which directly and indirectly affects their health. 3 A cohort study on Helsinki policemen found coronary heart disease as a major cause of mortality among policemen. 4 Obesity, dietary factors, smoking, alcohol use, exposure to stress at work and lack of physical activity were important factors associated with hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 the prevalence was higher than Chennai study (62.9%) 19 and Kerala study(66%). 2 Most of the police personnel (63.3%) had a waist circumference > 85 cm as compared to 71.5% and 65.1% (Waist Circumference > 90 cm) reported by Ramakrishnan et al 20 and Shabana et al 19 respectively.…”
Section: Discussionmentioning
confidence: 90%
“…1,2 It has been reported by researchers that due to enormous stress, police officers suffer from different physiological disorders, such as gastrointestinal, insomnia, psychological disorders,family dysfunction 1,[3][4][5][6][7][8][9] and cardiovascular disorders 10,11 than the general population. The objective of the study was to estimate the burden of individual and aggregated CVD risk factors and predict the 10 year risk of fatal and non-fatal cardiovascular event in this population using Framingham risk score.…”
Section: Introductionmentioning
confidence: 99%